An Academic Administration Model for the Basic School under a Jurisdiction of the Bangkok Secondary Educational Service Area Office 2 - Suksukon, Anusara; Sikkhabandit , Sowwanee; Theerawitthayalert, Panya (Interdisciplinary Academic and Research Journal, 2023)
Education is one of the most important foundations for creating progress and solving various problems in society. Because education is a process that will help people develop themselves in various ways that can live and work happily, knowingly, knowingly changing, can be a creative force for the sustainable development of the country. The purpose of this research was to develop a model for academic administration of basic education institutions under the Bangkok Secondary Educational Service Area Office 2, by doing 3 steps: 1) to study the current situation and guidelines for academic administration of educational institutions by using a questionnaire with 138 school directors, Director for academic affairs and assistant director and teachers of the School using a semi-structured interview form to interview 2 school directors. who received gold " OBEC AWARDS" on management. 2) Formation by studying, analyzing, and synthesizing relevant documents and research as concerning the results of a general situation analysis and use of appropriateness and validity assessment forms with 5 experts in academic administration. 3) The model and manual were used for a period of 1 month in 1 school by 12 school personnel involved in the model experiment and assessed the possibilities and benefits of the model with 30 persons. The research results were as followings: 1) The current state of the schools’ academic administration in every aspect was at the highest level. 2) The developed model consists of 2 main components: Component 1: The scope of academic administration consists of 7aspects: school curriculum development; learning process development; assessment; media, learning resources, and technology development; research for quality education improvement; internal quality assurance system development; and educational supervision It is driven by the second component the 4-step management process, namely planning, organizing, leading and control. 3) Experiment and evaluation in terms of feasibility and usefulness of the model, it was found at the highest level.